Enterprising Somali refugees in Cape Town: beyond informality, beyond the spaza shop - Hassan, Abdullahi Ali (Department of Environmental and Geographical Science, 2020)
Since the dawn of democracy, South Africa has received high numbers of refugees from around the African continent in particular. One of the largest groups of refugees, Somalis, have established numerous enterprises in South African cities, concentrated in micro and small business sectors, particularly in the grocery and textile industries. The presence of Somali entrepreneurs and their role in the South African economy is contested, framed in relation to township informal economies and debates on xenophobia. Research to-date, however, focuses almost exclusively on Somali informal micro-enterprises in the spaza shop sector. To address this gap in the research and debate, this thesis examines Somali entrepreneurs, their development of varied formal enterprises, and their business strategies. I demonstrate in that these small formal businesses operate beyond the micro township-based informal spaza sector, building networks between township and city formal economies, and linking multiple economic sectors. In doing so, they act as a medium between producers of goods and general city consumers. The research demonstrates that Somali immigrant entrepreneurs can be considered what Bonacich (1973) describes as “middleman minorities.” This argument builds on qualitative research in Cape Town with Somali refugees who own formal small businesses that employ between five and a hundred employees. I draw on their histories, examine the evolution of their businesses, to substantiate how as newcomers - refugees, with limited knowledge about South African business dynamics, and little access to resources of the country - they managed to find their feet in business in varied ways. I show how Bellville as Cape Town’s Little Mogadishu, acts as a business hub and melting pot, a place to meet, to work together and connect their businesses to the rest of the city. From these histories, experiences, and networks, I analyse the business strategies that Somali entrepreneurs draw on, which include partnerships, shareholding, the building of trust, and their own mobility. I also investigate what enabled them to get a foot in the door when they first arrived, find new business opportunities, and access new markets in the city, region, and in some cases beyond. I argue that Somali immigrant entrepreneurs have created a diverse set of complex formal businesses, ranging from the sale of textiles, the processing of animal products, to consumer household goods. Through these businesses, these entrepreneurs have created jobs, new economic networks, new products, and extended markets, as well as physical retail and wholesale spaces. In making this argument, this research offers a better understanding of entrepreneurial work and its logics in the Cape Town Somali immigrant community. Their own experiences as entrepreneurs, as well as their business strategies, exceed by far narratives of informality, the spaza shop sector, and experiences of violence and xenophobia. This research broadens understandings of immigrant entrepreneurial activity in South African cities, and shift existing negative perceptions that depict refugees and immigrants as burdens on host communities and cities. I hope the research might also help inform the formulation of relevant policies for transitioning informal micro-enterprises in the country into small formal enterprises, one strategy that might address the critical issue of high unemployment in South African cities and society.